Status of available major and micro nutrients in soils of Kelapur block, Yavatmal district, Maharashtra - JANGIR, ABHISHEK; SHARMA, R. P.; TIWARI, G.; VASU, D.; CHATTARAJ, S.; DASH, B.; MALAV, L. C.; CHANDRAN, P.; SINGH, S. K.; KUCHANKAR, H. (Journal of Soil and Water Conservation, 2019)
The study was conducted to evaluate the major and micronutrient status of Kelapur block, Yavatmal district, Maharashtra. A total of 3436 soil samples were collected by gird method (325Ã—325 interval) at a depth of 0-15 cm and analyzed for soil pH, electrical conductivity (EC), organic carbon (OC), available nitrogen (N), phosphorus (P), potassium (K), sulphur (S) and micronutrients (Fe, Mn, Cu and Zn). Soils were neutral to slightly alkaline (pH 6.6 - 8.8) and non-saline (EC <1 dSm-1). OC was medium to high with a mean value of 0.83%. Among the nutrients, available N was invariably deficient (100%) and deficiency of available Zn (70%), S (59.7%), P (37.6%) and Fe (27.9%) were observed. The available K was generally high with a mean of 694 kg ha-1 and Mn and Cu were sufficient. Coefficient of variation (CV) indicated that P, K, S, Fe, Mn, Zn and Cu varied highly (CV > 35%) whereas the variability of pH and N was low (CV < 15%). The nutrient index value (NIV) for N and S were low (1.0 and 1.5), medium for P (1.89) and high (2.86) for K. The generated nutrient status information can serve as an effective tool for farmers and policy makers in adoption of site specific nutrient management practices.